2003
DOI: 10.1080/10586458.2003.10504506
|View full text |Cite
|
Sign up to set email alerts
|

Computing the Pluricomplex Green Function with Two Poles

Abstract: CONTENTS 1. Introduction 2. Computing δ 3. Computing δ * 4. Numerical Computation of δ 5. Numerical Computation of δ * 6. Results of the Numerical Computation 7. A Counterexample to Coman's Conjecture Acknowledgments References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Recall that a partial positive answer in this case was found in [5] (see also [8]) in the case the poles were lying on D × {0}. In [20] numerical computations were carried out which strongly suggested that the equality in the case D = D 2 , N = 2, ν 1 = ν 2 should hold. The aim of this paper is to show that actually the Coman conjecture holds in the bidisk (D = D 2 ), N = 2, two arbitrary poles and ν 1 = ν 2 .…”
mentioning
confidence: 82%
“…Recall that a partial positive answer in this case was found in [5] (see also [8]) in the case the poles were lying on D × {0}. In [20] numerical computations were carried out which strongly suggested that the equality in the case D = D 2 , N = 2, ν 1 = ν 2 should hold. The aim of this paper is to show that actually the Coman conjecture holds in the bidisk (D = D 2 ), N = 2, two arbitrary poles and ν 1 = ν 2 .…”
mentioning
confidence: 82%